A framework of total constraint management for improving work flow in liquefied natural gas construction - Wang, J.; Shou, W.; Wang, Xiangyu (2015)
In complex and concurrent construction project, numerous constraints which come from engineering, supply chains and construction work face are the main factors affecting plan reliability. Effective management of these constraints is critical to improve planning reliability and work flow. However, current constraint management approach is very fragmented and heavy relies on human's commitments and static data in constraint identification, tracking, assessment and removal. To tackle this problem, this paper proposes a framework of Total Constraint Management (TCM), which possesses four superior characteristics including: (1) collaborative constraint identification; (2) real-time constraint status tracking; (3) dynamic constraint removal; and (4) visual constraint representation. Advanced technologies, such as Building Information Modelling, barcode, and Radio Frequency Identification, are discussed to enable TCM implementation in practice. A controlled experiment was developed to demonstrate and evaluate the framework. The results showed that successful implementation of TCM could significantly improve plan reliability and construction productivity.